Sosialisasi Media Animasi Blue Cartoon Bahasa Inggris di SD IT Imam Syafii Pekanbaru - Oktadela, Resy; Elida, Yusti; Mustika, Dea; Hadiyanti, Putri Octa; Yuliani, Sri; Ismail, Syofianis; Maulana, Rezky (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effectiveness of Blue Cartoon animation media in enhancing English language learning motivation at SD IT Imam Syafii Pekanbaru. The main obstacle faced in the English language learning process was the lack of intrinsic motivation among students, stemming from limited understanding of semantics and linguistic context. This condition requires educators to develop creative and innovative pedagogical strategies to increase the appeal of English language learning for students. The implementation of English-language Blue Cartoon animation video media had become one alternative learning strategy that can be applied. Through the use of internet technology, educators could access the YouTube platform to obtain various relevant English-language cartoon content. This research uses a qualitative method with a descriptive approach, where data collection was conducted through literature review. Literature review was a series of systematic procedures that include activities of reading, note-taking, and analyzing various literature sources to then be synthesized into findings and discussion. The results of data analysis indicate that the used of English-language Blue Cartoon animation media significantly increases interest and motivation for learning English among students at SD IT Imam Syafii Pekanbaru.